Multiscale modeling of steel fiber reinforced concrete based on the use of coupling finite elements and mesh fragmentation technique - Bitencourt, L. A. G. (2018)
A multiscale model is proposed based on the use of coupling finite elements recently developed by the authors. This feature allows the use of the same strategy to deal with two problems of non-matching meshes addressed in this work. One is regarding the coupling of discrete steel fibers into the bulk finite elements (overlapping meshes), and the other corresponds to the coupling of different subdomains of a concurrent multiscale model (non-overlapping meshes). Thus, for problems where the material failure concentrates in a specific region, the numerical model with a discrete treatment of fibers can be applied only in this region of interest, increasing the performance in terms of computation time. Using this approach for coupling non-matching meshes, a non-rigid coupling procedure is proposed to describe the complex nonlinear behaviour of the fiber-concrete interaction by adopting an appropriate damage constitutive model. To avoid the necessity of the widely used crack tracking schemes, a technique based on the insertion of special interface finite elements (three-node triangular or four-node tetrahedral elements) in between all regular finite elements of the mesh was applied. It can be shown that, as the aspect ratio of the interface element increases (ratio of the largest to the smallest dimension), the element's strains also increase approaching the same kinematics as the continuum strong discontinuity approach. As a consequence, standard continuum constitutive models, which tend toward discrete constitutive relations as the aspect ratio increases, can be applied to describe fracture process. Several tests are performed to show the applicability of the proposed scheme to build multiscale models and to predict the fracture process in steel fiber reinforced concrete.